Acompanhamento de usuários de aparelhos de amplificação sonora individual em um serviço de saúde auditiva: motivos do retorno e condutas associadas - Araujo, Tiago de Melo (2010)
Introduction: The problem of hearing loss mobilized health professionals, culminating in the establishment of PNASA (2004), which guaranteed full assistance for the hearing impaired. Thus, patients undergo a number of procedures during the process of selection and fitting of hearing aids through a service hearing healthcare professional. After nearly six years of implementation of PNASA, a growing number of patients seeking feedback on services, and often this is related return is simple procedures that can be readily achieved for the benefit of patients. This question envisioned the organization of an Emergency Care agenda as a strategy to meet this demand. Goal: Establish the demographic and audiological, identify and analyze the reasons of return and the respective managements as well as linking this analysis with the variables of time of use of HA and the time interval between the last day of the hearing evaluation and the Emergency Care. Method: The study included 440 subjects who met the selection criteria of the survey, conducted in DERDIC during the period of four months. These patients, who asked for return to service, were served through the emergency department, and the data collected through a specific form developed by the researchers. The outcome analysis was performed considering: audiological and demographic data of the subjects, the reason for return and pipelines generated. Results: With regard to demographic characteristics and audiologic of 440 subjects, we observed that 58.6% were female, 38.4% were elderly (over 60), 40.4% had schooling in primary school, 47 % had moderate hearing loss (in the better ear), 85% had sensorineural hearing loss bilaterally, 88.2% were users of BTE type hearing aid, 86.1% were using ears, 70.7% were use of hearing aids for the first time, 38.1% were using the hearing aid for a period of up to 12 months from the date of receipt of the devices and 65.5% reported use of hearing aids for a period equal to or greater than 8 hours / daily. The combinations occurring more reason to return and conduct, observed in 386 subjects were, respectively: O and O with 80% Ac and Ac with 58%, M and M 47.5%; Ass Ass and a 46% and Aj and Aj with 36.3%. Ducts Aj, M and O have been occurring for most subjects with shorter duration of use of hearing aids and shorter interval of time between the last day of the hearing evaluation and emergency department concurrently. Conclusion: The characteristics of the population that calls back to the Hearing Health Service DERDIC / PUCSP, reasons for returning and professional conduct, reflected significant implications for organization of processes involved in follow up of hearing aid users. A protocol for orientation in early use of hearing aids, the scheduling of follow up visits based on the date of last hearing evaluation and other changes in routine can result in better efficacy of the consultation, therefore greater benefit to the user of hearing aids, as well as improved quality of service provided